Finland : Financial Sector Assessment Program: Technical Note-Stress Testing the Banking System and Interconnectedness Analysis. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the results of stress testing of Finland's banking system. Despite high capitalization levels, there are important vulnerabilities in the Finnish banking system. Near-term risks are largely tilted to the downside, stemming from both external and domestic sources. A sharper-than-expected global growth slowdown would be a drag on Finland's export and GDP growth. Although so far high compared with the rest of the euro area banks, Finnish banks' profitability is facing challenges from the low interest rate environment and the low economic growth. Vulnerabilities include funding risks, contagion risks, and challenges related to long-term profitability.